MODEL PENGAMBILAN KEPUTUSAN PENERIMA BANTUAN SOSIAL MENGUNAKAN METODE WEIGHTED PRODUCT (WP) DAN TOPSIS DI KAMPUNG PURWAJAYA KECAMATAN BANJAR MARGO TULANG BAWANG - Sefriyanto, Eka; Nugroho, Handoyo Widi (LPPM AMIK Dian Cipta Cendikia, 2024)
This study aims to determine the steps or models of the WP method and the Topsis method and compare the results of the analysis of the two methods, This study aims to determine the steps or models of the WP method and the Topsis method. Low labor absorption and inadequate human resource capabilities make people's lives below the poverty line. Government efforts by launching various types of aid do not make poverty levels reduced. Some contributing factors include the provision of assistance that is not on target and the criteria used as a basis for assessments are not maximal. he selection of methods must be appropriate to anticipate errors in the data to be used. The Weighted Product (WP) method and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) part of Multi-Attribute Decision Making (MADM) are used to rank all alternatives of predetermined criteria and sub-criteria. The implementation of the two methods for the ten alternatives (Purwajaya village, Banjar Margo sub-district, Tulang Bawang district) turned out to give very good results. the calculation results of these two methods are different then it is concluded that the best results are Topsis with a value: 0.070137683.